Sports Commitment, Training Motivation, and Athletic Performance among Selected NCAA South Players - Verdejo, Michel N. (2024)
Participating in sports is essential for young people's life skills development. Adults are engaged in sports in the same ways that young people are—to maintain good health, enhance their interactions with others, and enhance their abilities (Cihan and Ilgar, 2019). Sports help young people develop their physical talents, and everyone who frequently participates in a sport appreciates the value of fitness and training in terms of how well they perform. This study's objective was to look into the level of sports commitment, training motivation, and athletic performance, probe the relationship between the athletes' level of sports commitment, training motivation, sports commitment, and athletic performance, and level of training motivation and athletic performance, and examine the predictive ability of the level of sports commitment, and training motivation, taken singly or in combination, of the level of athletic performance of NCAA players in the University of Perpetual Help System, Laguna. The findings revealed that the Athletes’ level of sports commitment along with personal goals, coach impact, and time and effort was “very high”, while the respondents’ level of sports commitment along with intrinsic and extrinsic was “very high”. On the other hand, the respondents’ level of athletic performance along with self-confidence, athletic ability, and, emotional ability was “very high”.  In addition, the athlete’s level of sports commitment in terms of time and effort, was significant to the level of training motivation in terms of intrinsic, respectively. In terms of respondents’ level of sports commitment in terms of coach impact was correlated to their level of athletic performance in terms of self-confidence, athletic ability, and emotional ability. It implied that these indicators had a substantial impact on athletes' performance. It is expected that this study could help establish and maintain a commitment to sports and motivation to achieve a high level of athletic performance.